Comparison of corneal dynamic parameters and tomographic measurements using Scheimpflug imaging in keratoconus. Issue 1 (30th May 2017) - Chan, Tommy CY; Wang, Yu Meng; Yu, Marco; Jhanji, Vishal
Abstract : Aim: To compare the diagnostic ability of corneal tomography and corneal dynamic response measurements in normal and keratoconus eyes. Methods: Consecutive patients with grade II–III keratoconus and age-matched normal subjects were recruited. Corneal imaging was performed using Pentacam (Oculus Optikgeräte, Wetzlar, Germany) and Corvis (Oculus Optikgeräte). A beta version of Corvis software was used with three additional parameters: maximal change of arc length, deformation amplitude (DA) ratio 1 and DA ratio 2. Diagnostic ability of both devices to differentiate normal and keratoconus eyes was evaluated using receiver-operating characteristic (ROC) curves. The areas under the ROC curve (AUC) and partial AUC (pAUC) for specificity ≥80% for each parameter of Corvis and final D value of Belin/Ambrosio Enhanced Ectasia Display (BAD) were compared. Results: Forty-two eyes of 42 patients (21 patients with keratoconus and 21 normal subjects) were included. Both groups were age matched (p=0.760). The ROC analysis showed that the final D value of BAD had the highest AUC (0.994) and pAUC (0.194). Maximum inverse radius had the highest AUC (0.954) but a relatively lower pAUC (0.158), while DA ratio 2 had the second highest AUC (0.946) together with the highest pAUC (0.177) among Corvis parameters. There was no significant difference between AUC and pAUC of BAD compared with those of DA ratio 1 (p≥0.162) and DA ratio 2 (p≥0.208). Conclusions: The results of our study suggest that Corvis measurements have the potential to differentiate keratoconus and normal eyes. The diagnostic ability of novel parameters on Corvis was comparable to Pentacam.